Strategi Peningkatan Partisipasi Masyarakat Dalam Program Kang Pisman Di Kota Bandung - Sitompul, Danil Julio; Laksmono, Bambang Shergi (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2024)
Community participation is an integrated part of collaborative governance. With collaborative governance, it can increase community participation in regional development and realize social welfare. The waste problem in the city of Bandung is caused by the low level of community participation in reducing waste in households and in the informal sector. So, a strategy is needed to increase community participation in the Kang Pisman program in Bandung City to increase public awareness in managing waste. The aim of this research is to see the strategy for increasing community participation in the Kang Pisman program in the city of Bandung by looking at 4 strategies through collaborative governance, community development, circular economy and digital-based governance approaches through waste processing. The research method used is qualitative with a descriptive research type as stated by Newman (2016). The results of this research indicate that the Strategy for Increasing Community Participation in the Kang Pisman program in Bandung City is going well. The strategy to increase community participation is not only influenced by the policies of the Kang Pisman program which uses a community development approach, but there are also triggering factors from the circular economy, increasing collaborative governance and socialization using digital.